Group of Twenty : Measures Which are Both Macroprudential and Capital Flow Management Measures. (Policy Papers; Policy Paper ;, 2015)
The global financial crisis underscored the costs of systemic instability at both the national and global levels and highlighted the importance of dedicated macroprudential and capital flow management policies. The IMF has been assisting its members with policy advice as well as developing and making operational their policy frameworks. Multilateral aspects of both policies need to be fully considered, including the interaction with other domestic and international legal frameworks. To the extent that capital flows are the source of systemic financial sector risks, the tools used to address those risks can be seen as both capital flow management measures (CFMs) and macroprudential measures (MPMs).